FUEL RECOMMENDATION INFORMATION SYSTEM (BBM) CASE STUDY: MINISTRY OF MARINE, FISHERIES AND FOOD OF NAGAN RAYA REGENCY - Nur Fadhillah; Muhammad Agam Thahir (Asian Journal of Aquatic Sciences, 2022)
The Department of Maritime Affairs, Fisheries and Food (DKPP) of Nagan Raya Regency is a fully authorized body in managing all fisheries, marine and food activities in Nagan Raya Regency, Aceh Province. One important factor in supporting the productivity of capture fisheries is fuel oil (BBM) for small and medium fishermen. The fulfillment of fuel for fishermen is influenced by the length of stay at sea, the distance to the fishing ground, the size of the vessel, the type of equipment used, the vessel used and the fuel used. The fuel recommendation information system for fishermen is influential as the carrying capacity of information effectiveness between the service and fishermen. The information system itself is a group of elements that are interconnected or interact to form a single unit with an approach using quantitative methods and participatory observation. make a solution to the DKPP Nagan Raya as an effort to create a BBM Information System Application with the aim of facilitating an information system or fuel data collection, data collection of fishermen, and data collection of fishermen's catches. The BBM Information System application with a click using the fisherman's android will be greatly facilitated in the BBM recommendation process because it is in accordance with the quota received. In addition, this application method also makes it easier to monitor and report fuel distribution to fishermen, because everything can be integrated and can be monitored directly by the Marine Fisheries Service of Nagan Raya Regency.